Ireland : 2019 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Ireland. (IMF Staff Country Reports; Country Report, 2019)
The Irish economy continues to expand strongly, benefitting from higher net exports by multinational enterprises and robust domestic demand. Accelerating wage growth reflects tight labor market conditions and inflation has started to pick up. Crisis legacies have diminished but some vulnerabilities persist. The outlook remains broadly positive, provided Brexit proceeds in an orderly manner. However, the economy operates near full capacity and an accelerating cyclical momentum could re-ignite a boom-bust dynamic. A no-deal Brexit represents the key downside risk, while escalation in global protectionism and sudden changes in corporate tax planning of multinational enterprises in Ireland could adversely affect the economy and public finances.